2019
DOI: 10.1002/hsr2.119
|View full text |Cite
|
Sign up to set email alerts
|

Decentralization and health resources transfer to local governments in Burkina Faso: A SWOT analysis among health care decision makers

Abstract: Background and Aims In line with the decentralization policy, in 2009, the central government of Burkina Faso issued a decree to transfer health resources to local governments for fulfilling their new responsibilities in health care provision. The first stage of this health care decentralization process involved the basic health care facilities, composed of primary health care facilities, maternities, dispensaries, maternal and child health centers, and essential drugs depots. This st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 22 publications
0
7
0
1
Order By: Relevance
“…45 In the literature around decentralization in health planning, studies have pointed to limited capacity and lack of accountability that often dictates the use and management of health resources at the local level. [46][47][48] Bossert had delineated five functional areas in which in which the degree of autonomy of local players ranges. 31 The study by Sheshadri found that Human Resource (HR) and financial management were perceived to be less autonomous leading the authors to recommend addressing capacity gaps of district functionaries.…”
Section: Discussionmentioning
confidence: 99%
“…45 In the literature around decentralization in health planning, studies have pointed to limited capacity and lack of accountability that often dictates the use and management of health resources at the local level. [46][47][48] Bossert had delineated five functional areas in which in which the degree of autonomy of local players ranges. 31 The study by Sheshadri found that Human Resource (HR) and financial management were perceived to be less autonomous leading the authors to recommend addressing capacity gaps of district functionaries.…”
Section: Discussionmentioning
confidence: 99%
“…There are studies that have similarly used qualitative study findings for SWOT analysis. [ 36 37 ] Eliciting opportunities and threats from qualitative studies could be a limiting one. Also, the study was limited to findings from only one district of Odisha, which could be greatly influenced by district and state specific practices.…”
Section: Discussionmentioning
confidence: 99%
“…SWOT can help policy- and decision-makers in different sectors plan and implement various policies and programs as well as decision processes [ 27 ]. SWOT is a suitable tool for identifying internal (strengths and weaknesses) and external factors (opportunities and threats) that can affect the policy or program under study, and facilitate analysis of the subject and decisions [ 28 ]. The purpose of using SWOT is to show the positive forces that are involved in a policy or program, and the problems and challenges that need to be identified and implemented in the future [ 29 ].…”
Section: Methodsmentioning
confidence: 99%